Do Bank Size Moderate Relationship between Banks’ Portfolio Diversification and Financial Performance of Commercial Banks in Kenya? - Stephen Githaiga Ngware; Tobias Olweny; Willy Muturi (SEISENSE Journal of Management, 2020)
Purpose- It is complicated to efficiently manage the bank’s portfolio, simultaneously maximize returns and minimize risks while being subject to managerial and regulatory constraints. In the financial industry, the size of a bank is used to assist in capturing economies as well as diseconomies of scale. Design/Methodology- As in cases of most literature from finance, natural logarithms of banks' total assets were made use of to measure commercial banks’ size. The 43 commercial banking institutions having an official license from CBK by December 2017 were the target population of this study. The study analyzed Time-Series Cross-Sectional unbalanced secondary panel data obtained from all the 43 commercial banking institutions in Kenya for fifteen years ranging from 2003 to 2017. Findings- Study findings revealed a positive effect of bank size on ROE and ROA that was significant. Correlation analysis revealed a positive association of bank size on the financial performance of banks in Kenya, which was significant. Bank size had a significant moderating effect on the relationship of banks portfolio diversification and financial performance of banks in Kenya. Practical Implications- The findings on bank size insinuated that a higher size of entire asset of banks is most probable to accelerate the bank to diversify into feasible opportunities on investment, traverse more enhanced lines of business, increase capacity in market power and, produce increased value that boosts the firm to profit from economies of scale and wider scope and henceforth superior and increased financial performance.